2017
DOI: 10.1186/s13030-017-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between salivary amylase and the physical and psychological changes elicited by continuation of autogenic training in patients with functional somatic syndrome

Abstract: BackgroundThe aim of this study was to clarify the changes in biological measures during autogenic training (AT) sessions and the relationship between these biological measures and the changes in physical and psychological measures induced by continuation of AT in patients with functional somatic syndrome (FSS). We used the salivary amylase (SAMY) level, skin temperature of the finger (TEMP), subjective symptom scores, and psychological characteristics to assess these changes.MethodsWe assessed 24 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(55 reference statements)
0
5
0
1
Order By: Relevance
“…Neurophysiological changes accompanying the autogenic state include a reduction in heart rate, vagal tone and salivary amylase levels [136,137], regulation of blood pressure [138] and an increase in muscle distension and peripheral vasodilatation [130,139]. A reduction in reticulo-cortical and thalamo-cortical activity is also observed, as well as immediate changes in structures connected to the reticular formation, such as the hypothalamus, cerebellum and limbic system, among others [139].…”
Section: Tablementioning
confidence: 99%
“…Neurophysiological changes accompanying the autogenic state include a reduction in heart rate, vagal tone and salivary amylase levels [136,137], regulation of blood pressure [138] and an increase in muscle distension and peripheral vasodilatation [130,139]. A reduction in reticulo-cortical and thalamo-cortical activity is also observed, as well as immediate changes in structures connected to the reticular formation, such as the hypothalamus, cerebellum and limbic system, among others [139].…”
Section: Tablementioning
confidence: 99%
“…In those situations, the therapist may use the autosuggestion of “your skin is calm and cool” as well as individually chosen phrases concerning the control of scratching . A recent study by Kiba et al . investigated the changes in biological measures during autogenic training sessions and the relationship between these biological measures and changes in physical/psychological changes in patients with functional somatic syndromes.…”
Section: Measurement Of Itchmentioning
confidence: 99%
“…Moreover, Wessely et al have suggested many other syndromes and symptoms, such as premenstrual syndrome and tension headache, for inclusion as FSS. 8 In our previous studies, we reported lower health‐related quality of life (HRQoL) associated with autonomic dysfunction 9 and improvement in somatic symptoms and mood disturbance through autogenic training 10 in patients with FSS. As it is usually less problematic for physicians to assess patients' physical dysfunction than their psychological conditions, the classification of FSS rather than MUS is expected to minimize misdiagnosis.…”
Section: Introductionmentioning
confidence: 98%